The Influence of Product, Price, Promotion and Distribution on the Marketing Strategy of Small and Medium Enterprises in Lhokseumawe City - Saharuddin Saharuddin; Khairil Anwar; Azhar Azhar (Management Research and Behavior Journal, 2022)
The study aims to determine the effect of product, price, promotion and distribution on the marketing strategy of small and medium enterprises located in Lhokseumawe City. For the purposes of data analysis, qualitative and quantitative methods are used. The data used is primary data.  The results of the study prove that partially, the variables of Product, Price, Promotion, Distribution affect the sales volume of Small and Medium Enterprises Products in Lhokseumawe City. Furthermore, the results of simultaneous testing prove that Ftabel of 3.00 is much smaller than F count of 11.044. The Correlation Coefficient (R) of 0.790 or 79.0%, this means that the Product, Price, Promotion and Distribution factors have a strong relationship with the marketing strategy of small and medium enterprises The Determination Coefficient (R2) of 0.624 or 62.4%, this means that small and medium business products are influenced by marketing strategies, the remaining 37. 6% is influenced by other variables outside this study, while the Adjusted R Square is 0.324 or 32.4%, this means that the Dependent Variable marketing strategy can be explained by variations in Product, Price, Promotion, Distribution which is an Independent Variable.